Correlation between Characteristics and Knowledge about Osteoporosis in Patients with Fragility Fractures at Saiful Anwar General Hospital - Irsan, Istan Irmansyah; Hariyanti, Tita; Isma, Satria Pandu Persada; Adiwignyo, Dandy Drestanto; Hamdani, Romi (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Osteoporosis is a global health issue. Fragility fractures, which occur due to minor trauma, are one of the serious consequences of osteoporosis. Aims: This study investigates the correlation between demographic characteristics and the level of knowledge about osteoporosis in patients with fragility fractures. This research used a descriptive design with a cross-sectional approach. The data was gathered through validated and reliable questionnaires. Respondents were patients with fragility fractures treated at Dr. Saiful Anwar General Hospital, Malang. Data analysis was performed using statistical tests to evaluate the correlation between age, gender, and knowledge about osteoporosis. The analysis revealed significant gender differences in osteoporosis knowledge (p-value = 0.037) but no substantial age-related disparities (p-value = 0.194). There were no significant differences in nutritional status based on gender (p-value = 0.881) or age (p-value = 0.521). Similarly, medication adherence showed no significant variance by gender (p-value = 0.883) or age (p-value = 0.589). Lastly, the understanding of osteoporosis did not significantly differ by gender (p-value = 0.467) or age (p-value = 0.782). In conclusion, the study reveals a significant gender disparity in osteoporosis knowledge, highlighting the need for tailored educational interventions and physician initiatives to ensure equitable awareness across diverse demographic groups.